Semantics of Worldly Life and Ascetic Life in the Thoughts of Hossein bin Saeed Ahwazi: A Review of the History of Shia Narrative Ethics in the Third Century - Abbas Mirzaei; NAZANIN AHMADI (اخلاق وحیانی, 2023)
This article examined the relationship between worldly life and asceticism based on Hossein bin Saeed Ahwazi's book entitled "Al-Zohd" (asceticism). These two concepts were on opposite sides of meaning and their practical overlap could be hardly found. In Imami narrative literature, asceticism had been recommended while the world was condemned. In general, muhaddith scholars had so well expressed the opposition of these two concepts in their works. However, it seemed that another approach could be taken to clarify the semantic agreement between asceticism and worldly life based on the narrative heritage of Shia, some signs of which could be observed in the famous book of "Al-Zohd" written by Hossein bin Saeed. This article tried to answer the question of what opinion Hossein bin Saeed had about asceticism and worldly life in the mentioned book. The review of the book "Al-Zohd" could strengthen the hypothesis that Hossein bin Saeed had a practical understanding between asceticism and worldly life contrary to the general view of the Shiite scholars. The reports he had cited from the imams revealed the fact that the ascetic could follow his mystic path while living worldly and concurrently controlling worldly desires in the framework of ascetic life. Indeed, he had presented a social discourse of the world that could be combined with ascetic life.